THE IMPACT OF ENVIRONMENTAL CHANGING, FOOD AVAILABILITY AND ANTROPOGENIC PRESSURE ON SARDINE (Sardinella lemuru) CPUE IN BALI STRAIT WATERS - Reny Puspasari; Puput Fitri Rachmawati; Eko Susilo; wijopriono wijopriono; Ngurah Nyoman Wiadnyana (Pusat Riset Kelautan, 2018)
As a dominant small pelagic fishery in Bali Strait waters, significant decrease of sardine (lemuru) production was bothering fisheries industries, particularly in Muncar and Pengambengan District in East Java and Bali province. Besides of over exploitation, changing environment condition such as temperature, salinity and thermocline depth, indicated the affect on decreasing of sardine production. The interaction among environment variabels, food source availability (Chl-a) and anthropogenic pressure (fishing effort) generate the number of sardine abundance showed by CPUE (Catch per Unit Effort) value that determined sardine production. The current research aims to analyze the simultant impact of changing environment, food availability and antropogenic pressure on sardine CPUE. Field research was conducted in Bali Strait where primary and secondary fisheries data were gathered at Muncar Fishing Port of Banyuwangi District East Java Province and Pengambengan Fishing Port of Jembrana District Bali Province. Oceanography data such as temperature, salinity, and chlorophyll-a profile were collected from INDESO Model. Data analysis was done by time series analysis of each variabels such as CPUE, SST and SSTA, thermocline depth, chl-a and also the number of trip. Partially analysis of those variabels was done by overlayed one another, and principal component analysis determined to analyze the effect of all those varibales simultaneously on sardine CPUE. Results show that there were an influenced of regional climate phenomenon on the dynamic of environment condition of Bali Strait waters, particularly IOD (Indian Ocean Dipole). The CPUE of sardine was determined by the interaction of environment variabels (SST/SSTA, salinity, thermocline depth), food source availabity (Chl-a) and antropogenic pressure (fishing trip) simultaneously, however SSTA gives a significant negative correlation on CPUE. Regional climate phenomenon might cause an extreme condition in Bali strait waters leading to unstable environment for sardine habitat. Drastically changing habitat condition occured under influenced of extreme condition would lead to disruption of sardine CPUE.